Digital pedagogical communication with higher education institutions: Analytical Reading - Abed, Salim; Dahdouh, Menia (Journal of Human Sciences, 2023)
The study aimed to discuss the theoretical literature related to pedagogical communication in the digital educational environment of higher education institutions, in order to identify the most important models and theories used in this context, and the changes that affected the elements of pedagogical communication, through describing and analyzing the theoretical frameworks for the variables of the study, ; A set of results has been reached, the most important of which are: Availability of information and knowledge in the process of higher education within the digital environment that frame this digital transformation and contribute to achieving effective pedagogical goals in student formation and making the knowledge content more flexible and appropriate to modern social requirements.